Examination of risk analysis of sow culling in a large-scale pig farm - Balogh, Péter; Ertsey, Imre; Kovács, Sándor (Acta Agraria Kaposváriensis, 2006)
Department of Economic Analysis and Statistics, Debrecen, H-4032 Böszörményi út 138. The authors examined the effect of genotype risk of culling at a pig farm in Hajdú–Bihar County. Data were collected about the lifetime of 1969 number of culled sows. Data were analysed by the survival analysis method. They concluded that there are close connection between the genotyp and the culling risk of the sows (as the productional lifetime goes by), and there are large differences in culling risk between genotypes.